MODULATORS OF THIOL-DISULFIDE IN THE CORRECTION OF ENERGY METABOLISM IN ACUTE CEREBRAL ISCHEMIA - Gorbacheva, S.V.; Belenichev, I.F.; Kucherenko, L.I.; Bukhtiyarova, N.V. (World of Medicine and Biology, 2015)
Аn important factor in normalization of mitochondrial functioning processes is a maintenance of thiol cellular redox status. Positive influence of thiol-disulfide system modulators explains the fact of their antioxidant action, namely the limitation of negative action of active oxygen forms on mitochondria. Presence of preparations of SH-groups in a molecule structure and their ability to bind cytotoxic derivatives in conditions of oxidative stress protect protein structures of a cell and transcription factors from the oxidative modification. Besides, these factors maintain redox homeostasis that prevents mitochondrial pore opening and formation of mitochondrial dysfunction.
Keywords: energetic metabolism; mitochondrial dysfunction; thiol-disulfide system modulators